2020
DOI: 10.1002/brb3.1804
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning ameliorated neuronal injury after middle cerebral artery occlusion by promoting neurogenesis

Abstract: Neuronal death and neurologic deficits are the major causes of disability in patients following cerebral infarction. Acute/programmed necrosis, autophagy, and apoptosis of brain neurons result from complex biochemical events triggered by stroke. Current treatments for cerebral infarction are limited; therefore, the development of effective treatment strategies would be of great value. At present, delivering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…It was demonstrated that ischemic stroke increased Nestin + cells in SVZ ( Figures 3C,D ) and DCX + /DAPI in both SVZ and DG ( Figure 4 ) ( p < 0.01). Apparently, the hypoxic condition induced proliferations of NSCs and neurogenesis, which was similar to those of previous reports ( Lin et al, 2015 ; Huang et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It was demonstrated that ischemic stroke increased Nestin + cells in SVZ ( Figures 3C,D ) and DCX + /DAPI in both SVZ and DG ( Figure 4 ) ( p < 0.01). Apparently, the hypoxic condition induced proliferations of NSCs and neurogenesis, which was similar to those of previous reports ( Lin et al, 2015 ; Huang et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…It was demonstrated that ischemic stroke increased Nestin + cells in SVZ (Figures 3C,D) and DCX + /DAPI in both SVZ and DG (Figure 4) (p < 0.01). Apparently, the hypoxic condition induced proliferations of NSCs and neurogenesis, which was similar to those of previous reports (Lin et al, 2015;Huang et al, 2020). LCH increased Nestin + , Nestin + /DAPI, and Nestin + /BrdU + in DG, and Nestin + /BrdU + in SVZ (p < 0.05), which implied that LCH promoted the proliferation of NSCs (Figure 3).…”
Section: Ligusticum Chuanxiong Hort Displays Significant Advantages On Neural Stem Cell Proliferation and Neurogenesissupporting
confidence: 90%
“…The sections were washed twice with distilled water and then 70% ethanol. Finally, the changes of nissl bodies were observed under a microscope [72]. For quantification, clear and intact neural cells with nissl bodies uniformly distributed around the nuclei in the hippocampal CA1 and DG regions were counted in a blinded manner.…”
Section: Nissl Stainingmentioning
confidence: 99%
“…For in vivo models, clinically relevant scenarios, such as cardiopulmonary resuscitation (CPR) [6,7], stroke [8] or myocardial infarction [9] in different species represent the basis to investigate the preconditioning hypothesis. This method's translation into clinics is debated.…”
Section: Introductionmentioning
confidence: 99%